Evaluasi Pelaksanaan Program Kampus Mengajar Batch 8 pada Mahasiswa Fakultas Teknik Universitas Negeri Padang - Hendra Warman; Budi Syahri; Waskito Waskito; Fiki Efendi (Lembaga Pengembangan Kinerja Dosen, 2025)
The Teaching Campus Program provides students with direct experience in collaborating with teachers and principals to improve the quality of learning, particularly in literacy, numeracy, and technology adaptation. This study aims to evaluate the implementation of the Teaching Campus Program Batch 8 among students of the Faculty of Engineering, Padang State University (FT UNP). This study uses a program evaluation research type with a quantitative approach. The research population consisted of 35 students, all of whom were sampled using total sampling technique. The research variable was the evaluation of the implementation of the Campus Teaching Program based on the CIPP (Context, Input, Process, Product) evaluation model. Based on the results of the study, the evaluation of the implementation of the Campus Teaching Program among FT UNP students was overall “Fairly Good”. This provides learning experiences outside the campus and improves student skills. However, efforts to improve the quality of each evaluation dimension, especially in terms of student placement relevant to their study programs, clarity of guidelines, and preparatory curriculum, are necessary to achieve the “Very Good” category and maximize the program's contribution.